Role of nanocrystal and Nanodots in food preservation: A prospective for food industry - Dharmendra Kumar; Pramod Kumar Sharma (Food and Humanity, 2026)

Synonymous variants in IRX4 and their association with congenital heart disease: an in-silico functional assessment - Jyoti Maddhesiya; Dharmendra Jain; Ashok Kumar; Bhagyalaxmi Mohapatra (Molecular Biology Reports, 2026)

Molecular crosstalk between miRNAs and lncRNAs in neurodegenerative disease pathways - Falguni Goel; Daksh Kumar; Payal Singh; Sachchida Nanda Rai; Dharmendra Kumar Yadav (Molecular Biology Reports, 2026)

Developmental block in ruminant embryos: Mechanisms, molecular insights and potential interventions - Srishti Bhatia; Manu Mangal; Priya Dahiya; Ashish Sindhu; Bhavya Maggo; Meeti Punetha; Prasoon Priyadarshi; Manoj Kumar Jena; Dharmendra Kumar (Animal Reproduction Science, 2026)

Long-term characteristics of the atmospheric boundary layer over the Himalayan Foothills using ground-based Lidar and reanalysis data - Arun Jangra; Som Kumar Sharma; Dharmendra Kumar Kamat; Shuchita Srivastava; Aniket Patel; Pooja Jindal; Prashant Kumar; Yogesh Kant; Debashis Mitra; Kondapalli Niranjan Kumar; R.P. Singh; Prakash Chauhan (Atmospheric Research, 2026)

Retrieval of wheat crop growth variables with novel frequency difference vegetation indices - Dileep Kumar Gupta; Sumit Kumar Chaudhary; Prashant K. Srivastava; Rajendra Prasad; Dharmendra Kumar Pandey (Advances in Space Research, 2026)

Atmospheric cloud detection and cloud base height estimation from the Lidar backscatter: a two-step statistical and machine learning approach - Aniket Patel; Yug Milind Thosar; Dharmendra Kumar Kamat; Som Kumar Sharma; Prashant Kumar; Arun Jangra (International Journal of Remote Sensing, 2026)

Climate–mining–water nexus: Contaminant processes, monitoring–modeling integration and adaptive management under climate variability - Amit Kumar; Gagan Matta; Rupesh Kumar; Dharmendra Singh Tomar (Environmental Research, 2026)

Comprehensive field-based hazard assessment and mitigation strategies of glacial lakes in the Eastern Himalaya - R. K. Sharma; Rajeev Rajak; Sandeep Tambe; Pranay Pradhan; Narpati Sharma; Baichung Lepcha; Priya Pradhan; Rajesh Kumar; Dhiren G. Shrestha; Dharmendra Lamsal; Sajan Poudyal; Tenzing D. Bhutia; et al. (Natural Hazards, 2026)

Phytochemistry and bioefficacy of Ageratum houstonianum leaf and flower essential oils: antioxidant, anti-inflammatory, and molecular docking studies - Prashant Kumar; Ananya Bahuguna; Kanchan Gairola; Rohit Pujari; Dharmendra Singh Rawat; Om Prakash; Ravendra Kumar; Shiv Kumar Dubey (Plant Biosystems, 2026)

Smartphone interfaced image based creatinine estimation on a novel micro pipette tip-based platform: Whole blood sample-to-creatinine readout - Shashank Kumar; Ujjawal Singh; Bisma Mushtaq; Ritu Singh; Dharmendra Kumar; Rishi Ram; Tarun Kumar; Vijay M. Shinde; Arnab Sarkar (Analytica Chimica Acta, 2026)

Botanical, traditional uses, phytochemical and biological potential of Strobilanthes (Acanthaceae) – A review - Vaishnavi Rawat; Ravendra Kumar; Poornima Bhatt; Stefania Garzoli; Pooja Bargali; Sakshi Negi; Avdhesh Kumar; Piyush Kumar; Shivangi Chamoli; Sneh Gautam; Dharmendra Singh Rawat (South African Journal of Botany, 2026)

Bioefficacy of plant growth promoting rhizobacteria (PGPR) in the sustainable management of root-knot nematodes in eggplant - Megha Sharma; Sunita Devi; Sumit Vashisth; Dharmendra Kumar; Subhash Chand; Kumari Manorma; Rakesh Kumar; Parmod Verma; Balbir Singh Dilta; Abhay (Physiological and Molecular Plant Pathology, 2026)

A Scalable Functional Nanogel of Polyacrylamide-Piperazine-Copper Oxide Nanoparticles for Enhanced Biogas Purification - Bibhuti Bhusan Sahoo; Mohd. Usama; Rahul Vyas; Dharmendra Kumar Bal (Bioresource Technology, 2026)

Intercomparison and Validation of SODAR and ERA5 Measured Atmospheric Boundary Layer Height Over Delhi - Nishant Kumar; Anjali S. Nair; Avni Tiwari; Kirti Soni; V. K. Soni; Anikender Kumar; Arvind Jha; Dharmendra Gupta (Journal of the Indian Society of Remote Sensing, 2026)

Investigation of the Mount Ruang volcanic eruption in Indonesia: a case study - Aniket Patel; Som Kumar Sharma; Ruchita Shah; Dharmendra Kumar Kamat; Prashant Kumar; Kondapalli Niranjan Kumar; Nupoor A. Chotaliya; Deepak Kumar Kar (Natural Hazards, 2026)

Evaluation of nematophagous and mycoparasitic potential of some nematode-trapping fungi against plant parasitic nematodes and fungal pathogen Rhizoctonia solani - Abhay Pratap Singh; Dharmendra Kumar; Chandra Mohan Singh (Australasian Plant Pathology, 2026)

TMC proteins regulate crop size and contraction dynamics during feeding in Drosophila - Dharmendra Kumar Nath; Subash Dhakal; Nabin Rana; Youngseok Lee (Insect Biochemistry and Molecular Biology, 2026)

Natural and Biological Products Therapeutic Potential in Restoring Gut Microbiome: Mechanistic Insights and Clinical Implications - Shanmukha K; Vasavi Pasupuleti; Krishna Yadav; Shubhamkumar M Baviskar; Madhulika Pradhan; Lalitkumar K. Vora; Dharmendra Kumar Khatri (Probiotics and Antimicrobial Proteins, 2026)
The gut microbiome is a complex ecosystem of trillions of microbes residing in the human gastrointestinal tract. This microbial community plays a pivotal role in human health by swaying various physiological processes like metabolism, immunomodulation, antimicrobial protection, and psychological health. Natural and biological products comprising herbal extracts, dietary fibers, probiotics, prebiotics, and synbiotics have long been documented for their potential to modulate gut microbiota composition and function. Understanding the interactions between natural products and gut microbiota can provide valuable insights into their health-promoting effects and therapeutic potential. Literature was systematically sourced, analyzed, and compiled through searches across databases such as Science Direct, Google Scholar, and PubMed. The search terms include “gut microbiome,” “Dysbiosis,” “probiotics,” “prebiotics,” “synbiotics,” “biological products,” “gut health,” “natural products,” “dietary fibers,” “resistant starches,” “clinical study reports,” “safety recommendations,” etc., and several combinations of these words. This article provides a deep insight into the overview of natural and biological products aimed at promoting a healthy gut microbiome. It underscores the functional roles of the gut microbiota, including nutrient metabolism, antimicrobial defense, and gastrointestinal tract integrity. Furthermore, it delves into the detailed mechanisms of action and clinical evidence supporting the use of probiotics, prebiotics, synbiotics, herbal extracts, and dietary fibers in modulating gut microbiota composition and function. The biological activity, detailed mechanism of action, safety, and their considerable potential as modulators of gut microbiota composition and function have been extensively studied. Further research is necessary to clarify the underlying mechanisms of action to investigate their clinical implications.

Investigation of Atmospheric Boundary Layer Dynamics Over the Himalayan Foothill Region: Insights from Ground-Based LiDAR Observations and WRF Model - Shuchita Srivastava; Sandhya Singh; Som Sharma; Pooja Jindal; C. Aparna; Yogesh Kant; Debashis Mitra; Dharmendra Kumar Kamat; Aniket Patel; R. P. Singh; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Monitoring the Atmospheric Boundary Layer Height Using Ceilometer Lidar Over the Northeast India - Partha Jyoti Sahu; Binita Pathak; Som Kumar Sharma; Barsha Dutta; Uday Bhattacharjee; Aniket Chakraborty; Aniket Patel; Dharmendra Kamat; Pradip Kumar Bhuyan; Arup Borgohain; Kalyan Bhuyan (Journal of the Indian Society of Remote Sensing, 2026)

Addressing the escalating threat of antimicrobial resistance (AMR) in fisheries and aquaculture - Mutum Deepti; Nitesh Kumar Yadav; Naresh Raj Keer; Dushyant Mahavadiya; Parvind Kumar; Madhulika; Dharmendra Kumar Meena (Aquaculture International, 2026)

Biochemical Variability in Indigenous Potato Varieties Under Storage Conditions and Across Different Sections - Bandana; Vineet Sharma; Dharmendra Kumar; V. K. Gupta; Brajesh Singh (Potato Research, 2026)

Emerging innovations in ophthalmic drug delivery for diabetic retinopathy: a translational perspective - Souvik Adak; Vaishnavi Suresh Jadhav; Dharmendra Kumar Khatri (Drug Delivery and Translational Research, 2026)

Seed Thermo Priming Improved Seedling Performance and Heat Tolerance by Modulating Physio-Biochemical Attributes in Lentil - Subramanian Poomani; Sangita Yadav; Ravish Choudhary; Dharmendra Singh; Anil Dahuja; Shiv Kumar Yadav (Agricultural Research, 2026)

Assimilation of Doppler weather radar data into WRF model using 3DVAR and 4DVAR assimilation methods for enhanced weather forecasting in the eastern Himalayas - Peeyush Gupta; M. Sudhanshu Shekhar; Gyan Prakash Singh; Dev Sen Gupta; Amit Kumar; Rupesh Kumar; Dharmendra Singh Tomar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Atmospheric boundary layer characteristics during severe air pollution and fog events over Delhi: Insights from ground-based Lidar, satellites, and models - Dharmendra Kumar Kamat; Som Kumar Sharma; Prashant Kumar; Kondapalli Niranjan Kumar; Sourita Saha; Aniket; Sukhwinder Kaur; Arun (Atmospheric Environment, 2026)

Dynamics of convective clouds near and below the lifting condensation level over a semi-arid Western-Indian region - Dharmendra Kumar Kamat; Som Kumar Sharma; Kondapalli Niranjan Kumar; Prashant Kumar; Sourita Saha; Hassan Bencherif (Atmospheric Research, 2026)

Characteristics of multi-layer clouds observed using ceilometer observations over Leh-Ladakh: A high-altitude cold desert region - Ruchita Shah; Som Sharma; Dharmendra Kamat; Kondapalli Niranjan Kumar; Prashant Kumar; Shantikumar S. Ningombam; Dorje Angchuk; Rohit Srivastava (Atmospheric Research, 2026)

Investigation of cloud characteristics over a high-altitude region, Mt. Abu, using ground-based Lidar and satellite observations - Dharmendra Kumar Kamat; Som Kumar Sharma; Prashant Kumar; Kondapalli Niranjan Kumar; Sourita Saha; Aniket (Theoretical and Applied Climatology, 2026)

Nrf2/Keap1 Signaling Axis in the Brain: Master Regulator of Oxidative Stress in Neurodegenerative and Psychiatric Disorders - Falguni Goel; Payal Singh; Sachchida Nand Rai; Dharmendra Kumar Yadav (Molecular Neurobiology, 2026)

Nrf2–Keap1 Pathway and NLRP3 Inflammasome in Parkinson’s Disease: Mechanistic Crosstalk and Therapeutic Implications - Ridhi Jain; Lalitkumar Vora; Deepak Nathiya; Dharmendra Kumar Khatri (Molecular Neurobiology, 2026)
Neurodegenerative disorders such as Parkinson’s disease (PD) are characterized by the progressive degeneration of dopaminergic neurons, which is driven primarily by oxidative stress and chronic neuroinflammation. Central to the cellular antioxidant defense system is the nuclear factor erythroid 2–related factor 2 (Nrf2)–Kelch-like ECH-associated protein 1 (Keap1) pathway, which mitigates oxidative damage and preserves mitochondrial integrity. Concurrently, the NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome acts as a key mediator of innate immune responses and has been increasingly implicated in neuroinflammatory cascades leading to neuronal loss in PD. Emerging evidence indicates a mechanistic interplay between the Nrf2–Keap1 axis and the NLRP3 inflammasome, wherein Nrf2 activation not only counteracts oxidative stress but also suppresses NLRP3-mediated inflammatory signaling. A comprehensive overview of the molecular crosstalk between the Nrf2 and NLRP3 pathways in the pathogenesis of PD, with emphasis on how impaired Nrf2 signaling exacerbates NLRP3 inflammasome activation, is provided. The preclinical and clinical findings on pharmacological agents that activate Nrf2 or inhibit NLRP3 as potential neuroprotective strategies in PD are also discussed. A growing body of evidence underscores the dual therapeutic benefit of targeting oxidative stress and inflammation via Nrf2 inducers and NLRP3 inhibitors. Nonetheless, obstacles such as restricted blood–brain barrier permeability, unintended effects, and variable clinical trial outcomes hinder the application of these findings in clinical settings. The advancement of disease-modifying therapies for PD hinges on continuous research aimed at deepening the mechanistic understanding of the Nrf2–NLRP3 axis and refining pharmacological strategies.

Serotonin drives fat storage via 5-HT7 signaling in Drosophila - Dharmendra Kumar Nath; Nabin Rana; Youngseok Lee (Genes & Genomics, 2026)

Multifunctional endospermic bacteria from cultivars of Triticum durum & T. dicoccum influencing plant growth - Jogdande SaiPrasad; Archna Suman; Dharmendra Kumar; Pushpendra Sharma (Archives of Microbiology, 2026)

Assessment and phycoremediation of Yamuna river contaminants originating from the Najafgarh Drain, India, using LC–MS - Dharmendra Kumar; Sanjukta Sahoo; Rounak Chourasia; Amit Kumar Rai; Dinabandhu Sahoo (Environmental Science and Pollution Research, 2025)

Effectiveness of polyacrylamide gel formulation for CO2 and H2S mitigation in biogas purification - Bibhuti Bhusan Sahoo; Mohd. Usama; Dharmendra Kumar Bal (Fuel, 2025)

First report on seasonal variations in chemical composition and pesticidal activities of Alpinia nigra rhizome essential oil - Shailja Singh; Om Prakash; Ravendra Kumar; Tanuja Kabdal; Stuti Arya; Shiv Kumar Dubey; Dharmendra Singh Rawat; Satya Kumar (Biochemical Systematics and Ecology, 2025)

Assessment and Remediation of Two Most Polluted Urban Sites of Yamuna River, India: An Algal-Based Approach - Pooja Baweja; Salam Sonia Devi; Dharmendra Kumar; Dinabandhu Sahoo (Water, Air, & Soil Pollution, 2025)

Population Structure and Diversity Analysis Using SSR Markers in Garden Pea (Pisum sativum L.): Implications in Breeding - Janani R.; Brij Bihari Sharma; Shri Dhar; Ajay Arora; Prakash Kumar; Harshawardhan Choudhary; Ramesh Kumar Yadav; Vinod Kumar Sharma; Amolkumar U. Solanke; Dharmendra Singh; Saurabh Singh (Plant Molecular Biology Reporter, 2025)

Evidence based molecular pathways, available drug targets, pre- clinical animal models and future disease modifying treatments of huntington’s disease - Falguni Goel; Vaishali Dobhal; Daksh Kumar; Sachchida Nand Rai; Dharmendra Kumar Yadav (Molecular Biology Reports, 2025)

Use of R848, a TLR 7/8 agonist to separate X and Y spermatozoa in buffalo: effects on cleavage rates, blastocyst production, and the ratio of male to female embryos - Mamta Meel; Mitesh Gaur; Meeti Punetha; Priya Dahiya; Manu Mangal; Renu Bala; Priyanka Ghanghas; Krishna Bansal; Dharmendra Kumar; R.K. Sharma; T.K. Datta; Pradeep Kumar (Theriogenology, 2025)

New insights unveiled: Identifying novel genomic regions governing zinc content in rice for enhanced biofortification - Abhinav Sao; Hemant Sahu; Ajit Kumar Mannade; Sunil Kumar Nair; Vinay Premi; Girish Chandel; Tarun Kumar Thakur; Amit Kumar; Rupesh Kumar; Dharmendra Singh Tomar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Long-Term Trend in Clouds and Precipitation Over an Urban City Ahmedabad in the Western-Indian Region - Dharmendra Kumar Kamat; Som Kumar Sharma; Prashant Kumar; Sourita Saha; Kondapalli Niranjan Kumar; Ruchita Shah (Journal of the Indian Society of Remote Sensing, 2025)

Reproductive vulnerability of Tenualosa Ilisha in the river Ganga: a climate-driven challenge - Basanta Kumar Das; Bandana Das Ghosh; Archisman Ray; Sourav Kumar Nandy; Hena Chakraborty; Arghya Kunui; Nabo Kumar Acharjya; Sanatan Paul; Amiya Kumar Sahoo; Santhana Kumar V; Dharmendra Kumar Meena (Environment, Development and Sustainability, 2025)

High-resolution analysis and prediction of heavy precipitation-induced GLOF events in North Sikkim Himalayas using the WRF model - Peeyush Gupta; M. Sudhanshu Shekhar; Gyan Prakash Singh; Dev Sen Gupta; Amreek Singh; Amit Kumar; Rupesh Kumar; Dharmendra Singh Tomar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Assessing the ecological preferences of planktic foraminifera from the south-eastern Arabian Sea - Kumari Anjali; Thejasino Suokhrie; Rajeev Saraswat; Sujata R. Kurtarkar; Dinesh Kumar Naik; Dharmendra Pratap Singh; Rupal Dubey (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Biofuel production from starchy crops: advanced technology and current perspectives - Dharmendra Kumar; Gitika Thakur; Pradeep Singh; Som Dutt; Vikas Mangal; Dinesh Kumar; Brajesh Singh (Archives of Microbiology, 2025)

Comparison of chemical composition, nematicidal activity and acetylcholinesterase inhibition with in silico mechanistic insights of Hedychium flavescens essential oils and extracts from aerial parts and rhizomes - Himani Karakoti; Pooja Bargali; Ravendra Kumar; Om Prakash; Satya Kumar; Stefania Garzoli; Dharmendra Singh Rawat; Jolanta Maslowiecka; Valery A. Isidorov (Biochemical Systematics and Ecology, 2025)

Epigenetic and Mitochondrial Metabolic Dysfunction in Multiple Sclerosis: A Review of Herbal Drug Approaches and Current Clinical Trials - Ashwani; Anjali Sharma; Mayank Kumar Choudhary; Dalapathi Gugulothu; Deepti Pandita; Surajpal Verma; Lalitkumar K. Vora; Dharmendra Kumar Khatri; Debapriya Garabadu (Molecular Neurobiology, 2025)
Multiple sclerosis (MS) is a complex autoimmune disease characterised by inflammation, demyelination, and neurodegeneration within the central nervous system (CNS). While the exact causes remain unclear, recent research highlights the significant role of epigenetic modifications and mitochondrial dysfunction in the disease’s onset and progression. Epigenetic alterations, such as DNA methylation, histone modification, and microRNA regulation, influence gene expression without altering the DNA sequence, leading to immune dysregulation and inflammation. Similarly, mitochondrial dysfunction, marked by impaired oxidative phosphorylation, reduced adenosine triphosphate (ATP) production, and increased reactive oxygen species (ROS), contributes to neurodegeneration and impaired remyelination in MS. The growing interest in targeting these two interconnected mechanisms has opened new avenues for MS treatment. Herbal drugs, known for their multi-targeted effects, have shown potential in modulating epigenetic markers and enhancing mitochondrial function. Compounds such as resveratrol, curcumin, epigallocatechin-3-gallate (EGCG), quercetin, and omega-3 fatty acids demonstrate potential in regulating DNA methylation, histone deacetylation, and mitochondrial biogenesis. These natural agents offer dual-action therapies by reducing oxidative stress and inflammation while promoting neuronal survival and remyelination. This review explores the therapeutic potential of herbal drugs targeting epigenetic and mitochondrial pathways in MS, evaluating their mechanisms of action and highlighting their promise as novel therapeutic agents. While initial findings are encouraging, further research and clinical trials are required to validate the efficacy of these herbal treatments and fully understand their potential in slowing disease progression and improving patient outcomes in MS. Such exploration could pave the way for safer, multi-targeted therapies, offering new hope in the management of MS and other neurodegenerative diseases.

Dynamics of mid-level stratiform clouds over the semi-arid regions of Western India: a post-monsoon case study - Dharmendra Kumar Kamat; Som Kumar Sharma; Prashant Kumar; Kondapalli Niranjan Kumar; Aniket Patel; Sourita Saha; Hassan Bencherif; Aditya Vaishya; Ruchita Shah (Modeling Earth Systems and Environment, 2025)

Topical delivery of baricitinib-impregnated nanoemulgel: a promising platform for inhibition of JAK -STAT pathway for the effective management of atopic dermatitis - Shweta Nene; Geetanjali Devabattula; Ganesh Vambhurkar; Kamatham Pushpa Tryphena; Dharmendra Kumar Khatri; Chandraiah Godugu; Pankaj Kumar Singh; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Red sorghum variety: A dual solution for functional food and grain mold resistance - C. Aruna; Kanti Meena; K.B.R.S. Visarada; K. Hariprasanna; C. Deepika; R. Venkateswarlu; I.K. Das; Dharmendra Kumar Meena; R. Madhusudhana; C. Tara Satyavathi (Journal of Cereal Science, 2025)

Study of genetic variability and emerging strains of Okra enation leaf curl virus: increasing risks to okra production in India - Ankit Kumar; Jyoti Singh; Anupma Singh; Dharmendra Pratap (Physiology and Molecular Biology of Plants, 2025)

Regulation of feeding and defecation in Drosophila by trpγ, piezo, and DH44R2 - Sonali Puri; Dharmendra Kumar Nath; Youngseok Lee (Insect Biochemistry and Molecular Biology, 2025)

A novel paradigm in the prediction of the performance of breeding buffalo bulls: role of hair cortisol and testosterone - Akanksha Gupta; Pradeep Kumar; Krishna Nand Bansal; Shubham Thakur; Usha Yadav; Renu Bala; Mamta Meel; Manju Bala Bishnoi; Shivani Bhardwaj; Nisha Verma; Meeti Punetha; Dharmendra Kumar; et al. (Tropical Animal Health and Production, 2025)

First report and molecular identification of two new begomovirus strains linked to okra enation leaf curl disease in northern and southern India - Ankit Kumar; Dharmendra Pratap (Australasian Plant Pathology, 2025)

Bioactive flavonoids from Leucosceptrum canum with nematicidal efficacy and mechanistic insights through acetylcholinesterase inhibition and docking study - Himani Karakoti; Ravendra Kumar; Om Prakash; Anamika Dhami; Satya Kumar; Dharmendra Singh Rawat (Pesticide Biochemistry and Physiology, 2025)

Application of Cellulase From Mutated Aspergillus sp. for the Production of Sustainable 2G Ethanol From Sugarcane Bagasse - Satwika Das; Dharmendra Shakya; Ramandeep Kaur; Naveen Kumar B; Chandukishore T; Surajbhan Sevda; Rangabhashiyam Selvasembian; Ashish A. Prabhu (BioEnergy Research, 2025)

Chemometric Assessment of Anthropogenically Impacted Ancient Artificial Wetland, Bhojtal, India, for its Drinking Water Suitability and Hydrogeochemical Classification - Rakesh Kumar; Md Basit Raza; Sangeeta Lenka; Simanku Borah; Anil Kumar Yadav; Dinesh Kumar Yadav; Roomesh K. Jena; Dhruba Jyoti Sarkar; Dharmendra Singh; Narendra Kumar Lenka; Rameshwar S. Kanwar; Sullip Kumar Majhi; et al. (Water, Air, & Soil Pollution, 2025)

Amelioration of breast cancer therapies through normalization of tumor vessels and microenvironment: paradigm shift to improve drug perfusion and nanocarrier permeation - Paras Famta; Saurabh Shah; Ganesh Vambhurkar; Giriraj Pandey; Deepkumar Bagasariya; Kondasingh Charan Kumar; Sajja Bhanu Prasad; Akshay Shinde; Suraj Wagh; Dadi A. Srinivasarao; Rahul Kumar; Dharmendra Kumar Khatri; et al. (Drug Delivery and Translational Research, 2025)

Waste not, want not: unlocking the innovative potential of organic and eco-friendly insect and algal resources for future aquaculture - Sourabh Debbarma; Suparna Deb; Nitesh Kumar Yadav; Shubham Kashyap; Payel Debbarma; Bagthasingh Chrisolite; Yilbong Yirang; Dharmendra Kumar Meena; Soibam Khogen Singh; Tanmoy Gon Choudhury; Arun Bhai Patel (Aquaculture International, 2025)

Investigation of atmospheric clouds and boundary layer dynamics during a dust storm in the Western-Indian region - Dharmendra Kumar Kamat; Som Kumar Sharma; Prashant Kumar; Kondapalli Niranjan Kumar; Aniket; Sourita Saha; Hassan Bencherif (Remote Sensing Applications: Society and Environment, 2025)

Modeling proppant transport and settlement in 3D fracture networks in geothermal reservoirs - Baohua Liu; Dharmendra Kumar; Ahmad Ghassemi (Geothermics, 2025)

High mobility group box 1 cytokine targeted topical delivery of resveratrol embedded nanoemulgel for the management of atopic dermatitis - Shweta Nene; Geetanjali Devabattula; Ganesh Vambhurkar; Kamatham Pushpa Tryphena; Pankaj Kumar Singh; Dharmendra Kumar Khatri; Chandraiah Godugu; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Sonophotocatalytic degradation of rhodamine B dye using Zr doped ZnO nanoparticles: Kinetic study and toxicity assessment - Kuldeep Roy; Dharmendra Kumar Bal; Kaiwalya Gawande; Priyesh Dhenge; Jaykumar Bhasarkar (Journal of Environmental Management, 2024)

A randomized, open-label two-period crossover pilot study to evaluate the relative bioavailability in the fed state of atovaquone-proguanil (Atoguanil™) versus atovaquone-proguanil hydrochloride (Malarone®) in healthy adult participants - Andrea Kuemmerle; Denis Gossen; Michael W. Marx; Ulrike Lorch; Maja Szramowska; Ashok Kumar; Dharmendra Singh; Satinder Singh; Hanu Ramachandruni; Byju Thankachen; Swapnil Kore; Myriam El Gaaloul; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Atoguanil™ is a novel complex of atovaquone (ATV) and proguanil (PG) with enhanced ATV bioavailability compared to Malarone®. This pilot study assessed whether the relative bioavailability (F rel ) of ATV, PG, and the primary PG metabolite cycloguanil (CG) following a single oral dose in the fed state of Atoguanil was similar to Malarone despite a 50% lower ATV dose. This open-label, single-dose, randomized 2-period, 2-treatment, balanced crossover study was conducted between 17th November 2021 and 18th March 2022. Eligible participants (aged 18–55 years) were randomized (1:1) in period 1 to Atoguanil (ATV/PG 500/348 mg) or Malarone (ATV/PG hydrochloride 1000/400 mg) administered following a high-fat, high caloric meal. After a 24-day washout period, participants crossed treatment arms. For the doses tested, F rel was assumed similar if 90%CIs were between 80 and 125% for the geometric mean ratio of the least square mean differences for each exposure parameter. In 15 evaluable participants, F rel was similar for ATV C max (93.6% [90%CI 83.6, 104.9]) but not AUC 0-inf (77.8% [67.4, 89.8]), for PG AUC 0-inf (95.6% [92.1, 99.2]) but not C max (82.4% [75.8, 89.5]), and for both CG C max (100.8% [95.0, 107.0]) and AUC 0-inf (102.9% [98.4, 107.7]). Nine adverse events occurred; all were of mild severity and not considered treatment related. At the doses tested, ATV F rel was lower following Atoguanil versus Malarone based on AUC 0-inf , though when adjusted for dose F rel increased by 156%. Both drugs were well tolerated with no safety concerns. ClinicalTrials.gov: NCT04866602 (April 26th, 2021)

Understanding molecular mechanisms and miRNA-based targets in diabetes foot ulcers - Urati Anuradha; Neelesh Kumar Mehra; Dharmendra Kumar Khatri (Molecular Biology Reports, 2024)

Potential Assessment of SAR and Optical Data with Machine Learning to Monitor Temporal Changes in Tall Vegetation - Kundan Rathore; Ajay Kumar Maurya; Dharmendra Singh (Journal of the Indian Society of Remote Sensing, 2024)

Sunflower mapping using machine learning algorithm in Google Earth Engine platform - Amit Kumar; Dharmendra Singh; Sunil Kumar; Nitin Chauhan; Sultan Singh (Environmental Monitoring and Assessment, 2024)

Cloud characteristics in the Aravalli ranges of Western India: Insights from ground-based Lidar measurements - Dharmendra Kumar Kamat; Som Kumar Sharma; Kondapalli Niranjan Kumar; Prashant Kumar; Sourita Saha (Bulletin of Atmospheric Science and Technology, 2024)

An improved DNA extraction method in okra for rapid PCR detection of Okra enation leaf curl virus from diverse Indian regions - Ankit Kumar; Jyoti Singh; Deepak Panwar; Anupma Singh; Ravi Singh Thapa; Rakesh Kumar; Dharmendra Pratap (Archives of Microbiology, 2024)

Tilapia lake virus: understanding incidence, enhancing resistance, and exploring seaweed therapies - Sourabh Debbarma; Nitesh Kumar Yadav; Ng Chinglembi Devi; Bagthasingh Chrisolite; Yilbong Yirang; Dharmendra Kumar Meena; Soibam Khogen Singh; Naresh Kumar Mehta; Bhargavi Priyadarshini Mocherla (Aquaculture International, 2024)

Establishment of CRISPR-Cas9 ribonucleoprotein mediated MSTN gene edited pregnancy in buffalo: Compare cells transfection and zygotes electroporation - Meeti Punetha; Sheetal Saini; Suman Choudhary; Surabhi Sharma; Renu Bala; Pradeep Kumar; R.K. Sharma; P.S. Yadav; T.K. Datta; Dharmendra Kumar (Theriogenology, 2024)

Techno-economics of high ash coal gasification: A machine learning approach using CatBoost model - Dharmendra Kumar Singh; Sandeep Kumar (Journal of Cleaner Production, 2024)

From orchard to table: Significance of fruit microbiota in postharvest diseases management of citrus fruits - Manoj Kumar Solanki; Zhen Wang; Amit Kaushik; Vipin Kumar Singh; Rajib Roychowdhury; Manish Kumar; Dharmendra Kumar; Joginder Singh; Sandeep Kumar Singh; Bhavana Dixit; Ajay Kumar (Food Control, 2024)

γ-Lactones in Canadian high arctic aerosols: Tracers for the oxidation of unsaturated fatty acids and intramolecular esterification of γ-hydroxyacids during polar sunrise - Dharmendra Kumar Singh; Kimitaka Kawamura; Ayako Yanase; Leonard Barrie (Atmospheric Environment, 2024)

Cymbopogon distans: A source of essential oil with potential antibacterial, antifungal, and mosquito-repelling properties - Swati Singh; Alka Kurmi; Vandana Singh; Munmun Kumar Singh; Suyashi Mishra; Uma Shankar; Aman Savita; Hariom Gupta; Narayan Prasad Yadav; Dharmendra Sakia; Ram Swaroop Verma (Food Bioscience, 2024)

Experimental Type 2 diabetes and lipotoxicity-associated neuroinflammation involve mitochondrial DNA-mediated cGAS/STING axis: implication of Type-1 interferon response in cognitive impairment - Kumari Preeti; Anika Sood; Valencia Fernandes; Islauddin Khan; Dharmendra Kumar Khatri; Shashi Bala Singh (Molecular Neurobiology, 2024)

Enhancing the quality of inferior oocytes of buffalo for in vitro embryo production: The impact of melatonin on maturation, SCNT, and epigenetic modifications - Nidhi Kumari; Sheetal Saini; Swati Thakur; Surabhi Sharma; Meeti Punetha; Pradeep Kumar; Chakarvati Sango; R.K. Sharma; T.K. Datta; P.S. Yadav; Dharmendra Kumar (Tissue and Cell, 2024)

Improved soil moisture estimation and detection of irrigation signal by incorporating SMAP soil moisture into the Indian Land Data Assimilation System (ILDAS) - Arijit Chakraborty; Manabendra Saharia; Sumedha Chakma; Dharmendra Kumar Pandey; Kondapalli Niranjan Kumar; Praveen K. Thakur; Sujay Kumar; Augusto Getirana (Journal of Hydrology, 2024)

Comparative investigation on chemical and green synthesized titanium dioxide nanoparticles against chromium (VI) stress eliciting differential physiological, biochemical, and cellular attributes in Helianthus annuus L. - Dharmendra Kumar; Safoora Mariyam; Kapuganti Jagadis Gupta; Muthu Thiruvengadam; Gajanan Sampatrao Ghodake; Baoshan Xing; Chandra Shekhar Seth (Science of The Total Environment, 2024)

Essential oils work synergistically to mitigate pathogenic impact of Meloidogyne incognita, Rhizoctonia solani and Sclerotinia rolfsii - Pooja Bargali; Ravendra Kumar; Ayush Devrani; Sonu Kumar Mahawer; Himani Karakoti; Om Prakash; Shilpi Rawat; Satya Kumar; Dharmendra Singh Rawat; Shiv Kumar Dubey; Chandra Shekhar Seth; Faheem Ahmad (Biocatalysis and Agricultural Biotechnology, 2024)

Sulfo-butyl ether β-cyclodextrin inclusion complexes of bosutinib: in silico, in vitro and in vivo evaluation in attenuating the fast-fed variability - Saurabh Shah; Paras Famta; Ganesh Vambhurkar; Deepkumar Bagasariya; Kondasingh Charan Kumar; Dadi A. Srinivasarao; Nusrat Begum; Anamika Sharma; Syed Shahrukh; Naitik Jain; Dharmendra Kumar Khatri; Saurabh Srivastava (Drug Delivery and Translational Research, 2024)

Multipath phase based vegetation correction scheme for improved field-scale soil moisture retrieval over agricultural cropland using GNSS-IR technique - Sushant Shekhar; Rishi Prakash; Dharmendra Kumar Pandey; Anurag Vidyarthi; Prashant K. Srivastava; Deepak Putrevu; Nilesh M. Desai (Advances in Space Research, 2024)

Immunomodulatory effect of saponin treatment and microbial infections provoke the expression of Mx gene in catla (Labeo catla) - Soumya Prasad Panda; Dhananjay Soren; Pragyan Roy; Debasmita Mohanty; Dharmendra Kumar Meena; Amiya Kumar Sahoo; Basanta Kumar Das (Aquaculture International, 2024)

Genetic characterization of minor carp (Labeo gonius) from Indian rivers revealed through mitochondrial ATPase 6/8 and D-loop region analysis: implications for conservation and management - Suvra Roy; Bijay Kumar Behera; Ramya V. L.; Ajay Kumar Rout; Vikash Kumar; Pranay Kumar Parida; Asim Kumar Jana; Pronob Das; Dharmendra Kumar Meena; Dibakar Bhakta; Absar Alam; Basanta Kumar Das; et al. (Frontiers in Marine Science, 2024)
India is the habitat of many freshwater fish species that make a significant contribution to endemism. However, the native species population is declining at a very fast rate due to pollution, habitat loss or degradation, new species introduction, hydrologic alterations, and overfishing. The minor carp, Labeo gonius , is one of the important fish species in the Indian river systems and holds enormous potential in culture fisheries. Therefore, the precise status of population structure is a prerequisite for the management of the species. In the present study, we assessed the potential of mtDNA ATPase 6/8 and D-loop regions as markers to determine the genetic diversity and phylogeography of L. gonius from Indian rivers. We have selected five major Indian rivers for investigation which could represent geographically distant populations of the studied fish. A total of 210 ATPase 6/8 sequences (842 bp) and 203 D-loop region sequences (683 bp) of L. gonius from the five major Indian rivers were submitted to NCBI. Results revealed that ATPase 6/8 has 17 haplotypes and 70 polymorphic sites with an overall haplotype diversity of 0.560 ± 0.036 and nucleotide diversity of 0.00347 ± 0.00. Furthermore, D-loop analysis revealed 58 haplotypes, 67 polymorphic sites, 0.954 ± 0.006 overall haplotype diversity, and 0.01914 ± 0.00 nucleotide diversity. The hierarchical AMOVA analysis indicated that a high proportion of the genetic variation (76.46% and 70.22% for the D-loop and ATPase 6/8 regions, respectively) was attributed to among-population variation under gene pool-1 (considering all the stocks from Ganga, Brahmaputra, Teesta, Narmada, and Mahanadi as a single pool). Furthermore, in gene pool-2, samples were divided into two groups: group 1 (Himalayan rivers)—Ganga, Brahmaputra, and Teesta; and group 2 (peninsular rivers)—Narmada and Mahanadi. Genetic variations in the D-loop and ATPase 6/8 regions were found among populations within groups at 70.65% and 53.48%, respectively. Haplotype network analysis revealed that there were significant differences in distributions and frequencies. The observed unique haplotypes might be useful for differentiating the stocks. In brief, the present study suggested that the D-loop and ATPase 6/8 regions are potential markers and represent a significant contribution to the genetic characterization of the minor carp L. gonius from major Indian rivers. Moreover, the L. gonius population along the east coast especially in the Himalayan rivers (Ganga, Brahmaputra, and Teesta river basin) is found to be genetically more diverse. The results would provide a scientific basis for the assessment of fisheries resources and management of this important species.

Effectiveness of various nematode-trapping fungi for biocontrol of the Meloidogyne incognita in tomato (Lycopersicion esculentum Mill.) - Dharmendra Kumar (Rhizosphere, 2024)

Review on interactions between nanomaterials and phytohormones: Novel perspectives and opportunities for mitigating environmental challenges - Dharmendra Kumar; Ritu Singh; Sudhir K. Upadhyay; Krishan K. Verma; Ravi Mani Tripathi; Haitao Liu; Om Parkash Dhankher; Rudra Deo Tripathi; Shivendra V. Sahi; Chandra Shekhar Seth (Plant Science, 2024)

Physiological and biochemical responses of garden pea genotypes under reproductive stage heat stress - R. Janani; Brij Bihari Sharma; Shri Dhar; Ajay Arora; Harshawardhan Choudhary; Ramesh Kumar Yadav; Dharmendra Singh; Dinesh Singh; Amolkumar U. Solanke; Prakash Kumar (Genetic Resources and Crop Evolution, 2024)

Recent advances in Bacillus-mediated plant growth enhancement: a paradigm shift in redefining crop resilience - Anil Patani; Margi Patel; Shaikhul Islam; Virendra Kumar Yadav; Dharmendra Prajapati; Ajar Nath Yadav; Dipak Kumar Sahoo; Ashish Patel (World Journal of Microbiology and Biotechnology, 2024)

Assessment of Physiochemical Parameters and Bioremediation of Complex Contaminated Yamuna River, India: An Algal-Based Approach - Dharmendra Kumar; Dinabandhu Sahoo (Water, Air, & Soil Pollution, 2024)

Methodological Breakdown of Potato Peel’s Influence on Starch Digestibility, In Vitro Glycemic Response and Pasting Properties of Potato - Milan Kumar Lal; Rahul Kumar Tiwari; Awadhesh Kumar; Ravinder Kumar; Dharmendra Kumar; Arvind Jaiswal; Sushil Sudhakar Changan; Som Dutt; Jelena Popović-Djordjević; Brajesh Singh; Jesus Simal-Gandara (American Journal of Potato Research, 2024)
A Potato ( Solanum tuberosum L.) is a major staple food consumed worldwide. Potato peel is an important constituent that is generally discarded and considered agricultural waste before processing or cooking. The present investigation is an attempt to utilize different contents of potato peels (PP) with potato flesh (PF) of processing cultivar (Kufri Chipsona 3) and table cultivar (Kufri Jyoti), which affect starch nutritional profile, glycemic response, and pasting properties. The combination of PP at different concentrations of 5, 10, and 15%, respectively, to PF showed a significant reduction ( P

Valorizing waste to wealth: a blue revolution in environmental science - Dharmendra Kumar Meena; K. N. Mohanta; Amiya Kumar Sahoo; Soibam Khogen Singh; Naresh Kumar Mehta (Environmental Science and Pollution Research, 2024)

Ecosystem-based fishery enhancement through pen culture of Indian major carp Labeo catla in a tropical floodplain wetland of North Eastern Region, India, during COVID pandemic - Simanku Borah; Basanta Kumar Das; Birendra Kumar Bhattacharjya; Anil Kumar Yadav; Pronob Das; Shyamal Chandra Sukla Das; Dharmendra Kumar Meena; Pranaya Kumar Parida; Mishal Puthiyottil; Raju Baitha; Jeetendra Kumar; Bhrigumani Dewan; et al. (Environmental Science and Pollution Research, 2024)

Evaluation of postnatal growth, hematology, telomere length and semen attributes of multiple clones and re-clone of superior buffalo breeding bulls - P.S. Yadav; Dharmendra Kumar; Monika Saini; R.K. Sharma; Seema Dua; Naresh L. Selokar; Sonu Bansal; Meeti Punetha; Akanksha Gupta; Rajesh Kumar; Pradeep Kumar (Theriogenology, 2024)

Mito-Q supplementation of in vitro maturation or in vitro culture medium improves maturation of buffalo oocytes and developmental competence of cloned embryos by reducing ROS production - Maninder Sharma; Meeti Punetha; Sheetal Saini; Suman Chaudhary; Sujata Jinagal; Swati Thakur; Pradeep Kumar; Rajesh Kumar; R.K. Sharma; P.S. Yadav; Dharmendra Kumar (Animal Reproduction Science, 2024)

Characterization of a Regional Dust Storm Using RAMAN Lidar Over the Western Indian Region - K. K. Shukla; Som Kumar Sharma; Kondapalli Niranjan Kumar; Prashant Kumar; Dharmendra Kumar Kamat; Raju Attada; Sourita Saha (Journal of the Indian Society of Remote Sensing, 2023)

Response of the boundary layer clouds to the surface forcings: A case study of western India - Sourita Saha; Dharmendra Kumar Kamat; Som Sharma; Prashant Kumar; Kondapalli Niranjan Kumar; Hassan Bencherif; Shyam Lal; Satish Chandra (Remote Sensing Applications: Society and Environment, 2023)

Altitudinal variability in chemical profile and pesticidal properties of Zingiber roseum (Roxb.) Roscoe extracts - Sonu Kumar Mahawer; Ravendra kumar; Himani Karakoti; Om Prakash; Satya Kumar; Dharmendra Singh Rawat; Jolanta Maslowiecka; Valery A. Isidorov; Mozaniel Santana de Oliveira (Biochemical Systematics and Ecology, 2023)

A multi-scale algorithm for the NISAR mission high-resolution soil moisture product - Preet Lal; Gurjeet Singh; Narendra N. Das; Dara Entekhabi; Rowena Lohman; Andreas Colliander; Dharmendra Kumar Pandey; R.K. Setia (Remote Sensing of Environment, 2023)

Deep-sea benthic foraminiferal response to the early Oligocene cooling: a study from the Southern Ocean ODP Hole 1138A - Rakesh Kumar; Dharmendra Pratap Singh; Abhayanand Singh Maurya (Geo-Marine Letters, 2023)

Assessment of Nutritional Constituents Content and Biomedical Aspects of Five Gracilaria Species: A Multivariate Analysis - Dharmendra Kumar; Shivankar Agrawal; Manoj Kumar; Dinabandhu Sahoo (Journal of Aquatic Food Product Technology, 2023)

The current state of research and potential applications of insects for resource recovery and aquaculture feed - Soibam Khogen Singh; Lokesh Pawar; Akhil Joe Thomas; Reshmi Debbarma; Pradyut Biswas; Arati Ningombam; Ayam Gangarani Devi; Gusheinzed Waikhom; Arun Bhai Patel; Dharmendra Kumar Meena; Gunimala Chakraborty (Environmental Science and Pollution Research, 2023)

Correction to: Necrostatin-1 S mitigates type-2 diabetes-associated cognitive decrement and lipotoxicity-induced neuro-microglia changes through p-RIPK-RIPK3-p-MLKL axis - Kumari Preeti; Valencia Fernandes; Anika Sood; Islauddin Khan; Dharmendra Kumar Khatri; Shashi Bala Singh (Metabolic Brain Disease, 2023)

Diverse uses of valuable seafood processing industry waste for sustainability: a review - Jham Lal; Suparna Deb; Soibam Khogen Singh; Pradyut Biswas; Reshmi Debbarma; Nitesh Kumar Yadav; Sourabh Debbarma; Anand Vaishnav; Dharmendra Kumar Meena; Gusheinzed Waikhom; Arun Bhai Patel (Environmental Science and Pollution Research, 2023)

A new role of H89: Reduces capacitation-like changes through inhibition of cholesterol efflux, calcium influx, and proteins tyrosine phosphorylation during sperm cryopreservation in buffalo - Jasmer Dalal; Pradeep Kumar; R.K. Chandolia; Shikha Pawaria; Renu Bala; Dharmendra Kumar; P.S. Yadav (Theriogenology, 2023)

Titanium dioxide nanoparticles potentially regulate the mechanism(s) for photosynthetic attributes, genotoxicity, antioxidants defense machinery, and phytochelatins synthesis in relation to hexavalent chromium toxicity in Helianthus annuus L. - Dharmendra Kumar; Om Parkash Dhankher; Rudra Deo Tripathi; Chandra Shekhar Seth (Journal of Hazardous Materials, 2023)

Altitudinal and seasonal distribution of benthic macroinvertebrates in River Tons — a tributary of Yamuna River, Uttarakhand, India - Basanta Kumar Das; Arghya Kunui; Saurav Kumar Nandy; Amiya Kumar Sahoo; Dharmendra Kumar Meena; Samir Kumar Paul; Uttam Kumar Sarkar; Kausik Mondal (Environmental Monitoring and Assessment, 2023)

Comprehensive insight into altered host cell-signaling cascades upon Helicobacter pylori and Epstein–Barr virus infections in cancer - Dharmendra Kashyap; Samiksha Rele; Pranit Hemant Bagde; Vaishali Saini; Debi Chatterjee; Ajay Kumar Jain; Rajan Kumar Pandey; Hem Chandra Jha (Archives of Microbiology, 2023)

Mitochondria-targeted antioxidant MitoQ ameliorates ROS production and improves cell viability in cryopreserved buffalo fibroblasts - Meeti Punetha; Sheetal Saini; Suman Chaudhary; Renu Bala; Maninder Sharma; Pradeep Kumar; Dharmendra Kumar; P.S. Yadav (Tissue and Cell, 2023)

Necrostatin-1S mitigates type-2 diabetes-associated cognitive decrement and lipotoxicity-induced neuro-microglia changes through p-RIPK-RIPK3-p-MLKL axis - Kumari Preeti; Valencia Fernandes; Anika Sood; Islauddin Khan; Dharmendra Kumar Khatri; Shashi Bala Singh (Metabolic Brain Disease, 2023)

Understanding the breeding phenology of anadromous fish Tenualosa ilisha (Hamilton, 1822) in relation to climatic variables in Brahmaputra River, India - Simanku Borah; Amiya Kumar Sahoo; Vaisakh Gopinathapillai; Dharmendra Kumar Meena; Ashok Kumar Jaiswar; Geetanjali Deshmukhe; Anil Kumar Yadav; Pranab Gogoi; Debasmita Mohanty; Karankumar Ramteke; Birendra Kumar Bhattacharjya; Basanta Kumar Das (Frontiers in Marine Science, 2023)
The Hilsa, Tenualosa ilisha , commands a very high value as food fish. The present study was carried out to understand the breeding phenology of T. ilisha in relation to climatic variables. Monthly fish samples were collected from two landing centres, namely, Uzanbazar (Guwahati) and Shri Ramghat, Dhubri, of River Brahmaputra during May 2018 to April 2019. The assessment of gonadosomatic index (GSI) of T. ilisha revealed higher GSI values during October to February, and showed temporal variations with respect to sex. In males, highest GSI value was observed in the month January followed by February, whereas in females, GSI value was found to be highest in November followed by October. GSI (pooled) value was negatively correlated with air temperature, indicating vulnerability of the species to climate change. The highest percentage of mature males was observed during October–February, and mature females during October–December. The length at first maturity was recorded to be 290 mm for female(s) and 259 mm for male(s). The absolute fecundity ranged from 103,164 to 583,456 ova for fishes in the size range of 229–403 mm, with an average of 250,532 ova per female. Relative fecundity was found to range from 306 to 1096 ova per gram body weight, with an average of 791 ova per gram body weight. The diameter of ova of the studied fishes ranged from 414.6 to 738.2 µm, with a mean value of 546.73 ± 7.18 µm. The percentage frequency distribution of mature ova shows a distinct single peak or mode. Sex ratio (male: female) was found to be 1:0.87, indicating dominance of males over females. The chi-square test on observed sex ratio against the hypothetical ratio of 1:1 did not reveal a significant difference ( p > 0.05). The findings of the present study can provide impetus toward successful management of this highly prized, transboundary, and migratory resource of River Brahmaputra, in the context of changing climate.

Identification and in silico characterization of CSRP3 synonymous variants in dilated cardiomyopathy - Prerna Giri; Dharmendra Jain; Ashok Kumar; Bhagyalaxmi Mohapatra (Molecular Biology Reports, 2023)

Atmospheric Boundary Layer Over Ahmedabad, Western Indian Region: Impact of COVID-19 Nationwide Lockdown - Sourita Saha; Som Sharma; Abha Chhabra; Prashant Kumar; Niranjan K. Kondapalli; Dharmendra Kamat; Shyam Lal (Pure and Applied Geophysics, 2023)

Estimation of soil erosion in indo-gangetic region using revised universal soil loss equation (RUSLE) model and geospatial technology - Sunil Kumar; Dharmendra Singh; Amit Kumar; Mukesh Kumar; Kushal Giri; Kushala Devi; Sultan Singh (Modeling Earth Systems and Environment, 2023)

Application of sentinel-1 SAR-derived vegetation descriptors for soil moisture retrieval and plant height prediction during the wheat growth cycle - Rucha Dave; Koushik Saha; Amit Kushwaha; Dharmendra Kumar Pandey; Manisha Vithalpura; Nidhin Parath; Abishek Murugesan (International Journal of Remote Sensing, 2023)

3D Modeling of Hydraulic and Natural Fracture Interaction - Amirhossein Kamali; Ahmad Ghassemi; Dharmendra Kumar (Rock Mechanics and Rock Engineering, 2023)

Fingolimod Alleviates Cognitive Deficit in Type 2 Diabetes by Promoting Microglial M2 Polarization via the pSTAT3-jmjd3 Axis - Anika Sood; Valencia Fernandes; Kumari Preeti; Mayuri Khot; Dharmendra Kumar Khatri; Shashi Bala Singh (Molecular Neurobiology, 2023)

Molecular Insights into the Role of Reactive Oxygen, Nitrogen and Sulphur Species in Conferring Salinity Stress Tolerance in Plants - Vikas Mangal; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Ahsan Altaf; Salej Sood; Dharmendra Kumar; Vinay Bharadwaj; Brajesh Singh; Rajesh Kumar Singh; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Effect of Stocking Density on Growth, Water Quality Changes and Cost Efficiency of Butter Catfish (Ompok bimaculatus) during Seed Rearing in a Biofloc System - Snigdha S. Majhi; Soibam Khogen Singh; Pradyut Biswas; Reshmi Debbarma; Janmejay Parhi; Soibam Ngasotter; Gusheinzed Waikhom; Dharmendra Kumar Meena; Ayam Gangarani Devi; Sudhanshu S. Mahanand; K. A. Martin Xavier; Arun Bhai Patel (Fishes, 2023)
Biofloc technology is a modern-day high-density fish culture system employing heterotrophic conversion of nitrogenous waste into useful flocs for water quality control and improved welfare. However, optimization of the stocking density for the target species during seed rearing is the key to a successful farming operation. The study evaluated the effect of different stocking density on the growth, feed utilization, digestive physiology and economics in a biofloc-based seed rearing of butter catfish, O. bimaculatus. Advanced fry (1.21 ± 0.08 g) was reared in a zero-water exchange biofloc system for 90 days at stocking densities of 0.5 g/L(T1), 1.0 g/L(T2), 1.5 g/L(T3) and 2.0 g/L(T4). The observed water quality indicates a reduction in DO and pH in T4, while the total ammonia nitrogen and nitrite levels remained low in T1. Among the groups, highest weight gain was noticed in the lowest stocking density (0.5 g/L) (p

Environmental Characterization of Two Ecologically Distinct Gangetic Oxbow Lakes using Zooplankton Taxonomic Indices Through Comparative Approach for Wetland Monitoring - Suman Kumari; Lianthuamluaia Lianthuamluaia; Uttam Kumar Sarkar; Mishal Puthiyottil; Gunjan Karnatak; Dharmendra Kumar Meena; Sandhya Kavitha Mandhir; Md Abul Hassan; Ashok Kumar Jaiswar; Anil Prakash Sharma; Basanta Kumar Das (Wetlands, 2023)

Towards the development of phytoextract based healthy ageing cognitive booster formulation, explored through Caenorhabditis elegans model - Rakesh Pandey; Dayanandan Mani; Karuna Shanker; Dnyaneshwar Umrao Bawankule; Debabrata Chanda; Raj Kishori Lal; Anirban Pal; Puja Khare; Narendra Kumar; Sudeep Tandon; Dharmendra Saikia; Anil Kumar Gupta; et al. (The Nucleus, 2022)

Nutritional, Processing and Sensorial Attributes of Organic and Inorganic Indian Potatoes - Pinky Raigond; Sanjay Rawal; Vandana Parmar; Asha Thakur; Bandana; Tanuja Mishra; Som Dutt; Arvind Jaiswal; Milan Kumar Lal; Sushil S. Changan; Dharmendra Kumar; Brajesh Singh (Potato Research, 2022)

Neuroepigenetic alterations in the prefrontal cortex of type 2 diabetic mice through DNA hypermethylation - Valencia Fernandes; Anika Sood; Kumari Preeti; Dharmendra Kumar Khatri; Shashi Bala Singh (Molecular Biology Reports, 2022)

Chemical composition and antimicrobial activity of the leaf essential oil of Ravenia spectabilis Engl. (Rutaceae) - Swati Singh; Alka Kurmi; Munmun Kumar Singh; Praveen Kumar Kashyap; Sudeep Tandon; Amit Chauhan; Rajendra Chandra Padalia; Dharmendra Saikia; Ram Swaroop Verma (Natural Product Research, 2022)

Analysis of bluetongue disease epizootics in sheep of Andhra Pradesh, India using spatial and temporal autocorrelation - Ravichandran Karthikeyan; Ramkumar N Rupner; Shiva Reddy Koti; Nagaraj Jaganathasamy; Michael V. Lalrinzuala; Sachin Sharma; Shikha Tamta; Rotluangkimi; Sukdeb Nandi; Yashpal Singh Malik; Zunjar Baburao Dubal; Dharmendra Kumar Sinha; et al. (Veterinary Research Communications, 2022)

Mercury occurrence in drinking water resources of Ganga Alluvial Plain, northern India - Vandana Devi; Mohammad Mohsin Atique; Garima Upreti; Jitendra Kumar Yadav; Satyendra Singh; Dharmendra Kumar Jigyasu; Munendra Singh (Sustainable Water Resources Management, 2022)

Impact of dust storm on the atmospheric boundary layer: a case study from western India - Sourita Saha; Som Sharma; Abha Chhabra; Kondapalli Niranjan Kumar; Prashant Kumar; Dharmendra Kamat; Shyam Lal (Natural Hazards, 2022)

Assessing spatio-temporal pattern of macrozoobenthic community in relation to water quality in a tropical Indian reservoir - Tasso Tayung; Lianthuamluaia Lianthuamluaia; Pritijyoti Majhi; Uttam Kumar Sarkar; Asit Kumar Bera; Dharmendra Kumar Meena; Basanta Kumar Das (Arabian Journal of Geosciences, 2022)

Transcriptional profile of cumulus associated GJA1, PTX3, PRSS35, and SERPINE2 genes with oocytes and embryonic development in water buffalo - Lalit Mohan Jeena; Dharmendra Kumar; Sandeep Rahangdale; Ajit Pratap Singh; Bikash Chandra Sarkhel (Molecular Biology Reports, 2022)

Prospecting potential of endophytes for modulation of biosynthesis of therapeutic bioactive secondary metabolites and plant growth promotion of medicinal and aromatic plants - Devendra Singh; Shobit Thapa; Himanshu Mahawar; Dharmendra Kumar; Neelam Geat; S. K. Singh (Antonie van Leeuwenhoek, 2022)

Identification of intrinsically disorder regions in non-structural proteins of SARS-CoV-2: New insights into drug and vaccine resistance - Farah Anjum; Taj Mohammad; Purva Asrani; Alaa Shafie; Shailza Singh; Dharmendra Kumar Yadav; Vladimir N. Uversky; Md Imtaiyaz Hassan (Molecular and Cellular Biochemistry, 2022)

Differential gene expression and network analysis in head and neck squamous cell carcinoma - Insan Habib; Farah Anjum; Taj Mohammad; Md Nayab Sulaimani; Alaa Shafie; Mazen Almehmadi; Dharmendra Kumar Yadav; Sukhwinder Singh Sohal; Md Imtaiyaz Hassan (Molecular and Cellular Biochemistry, 2022)

Salinity responses and tolerance mechanisms in underground vegetable crops: an integrative review - Kumar Nishant Chourasia; Sanket Jijabrao More; Ashok Kumar; Dharmendra Kumar; Brajesh Singh; Vinay Bhardwaj; Awadhesh Kumar; Sourav Kumar Das; Rajesh Kumar Singh; Gaurav Zinta; Rahul Kumar Tiwari; Milan Kumar Lal (Planta, 2022)

A molecular insight of inflammatory cascades in rheumatoid arthritis and anti-arthritic potential of phytoconstituents - Vaibhav Patidar; Shruti Shah; Rahul Kumar; Pankaj Kumar Singh; Shashi Bala Singh; Dharmendra Kumar Khatri (Molecular Biology Reports, 2022)

Amorphous systems for delivery of nutraceuticals: challenges opportunities - Devendrasingh Tomar; Pankaj K. Singh; Sajidul Hoque; Sheela Modani; Anitha Sriram; Rahul Kumar; Jitender Madan; Dharmendra Khatri; Kamal Dua (Critical Reviews in Food Science and Nutrition, 2022)

Strategies for maximizing utilization of de-oiled rice bran (DORB) in the fish feed - Amit Ranjan; Sarvendra Kumar; Narottam Prasad Sahu; Kamal Kant Jain; Ashutosh Dharmendra Deo (Aquaculture International, 2022)

Bacterial consortium for efficient degradation of di-ethyl phthalate in soil microcosm - Dharmendra Kumar; Livleen Shukla; Shashi Bala Singh; Lata Nain; Surender Singh (Environmental Sustainability, 2021)

Budding Multi-matrix Technology—a Retrospective Approach, Deep Insights, and Future Perspectives - Anitha Sriram; Suma Tangirala; Srividya Atmakuri; Sajid Hoque; Sheela Modani; Saurabh Srivastava; Srushti Mahajan; Indrani Maji; Rahul Kumar; Dharmendra Khatri; Jitender Madan; Pankaj Kumar Singh (AAPS PharmSciTech, 2021)

Morpho-physiological characterization coupled with expressional accord of exclusion mechanism in wild and cultivated lentil under aluminum stress - Chandan Kumar Singh; Dharmendra Singh; Shristi Sharma; Shivani Chandra; Jyoti Taunk; Noren Singh Konjengbam; Deepti Singh; Arun Kumar; K. C. Upadhyaya; Madan Pal (Protoplasma, 2021)

Biotite as a geoindicator of rare earth element contamination in Gomati River Basin, Ganga Alluvial Plain, northern India - Priyanka Singh; Jitendra Kumar Yadav; Dharmendra Kumar Jigyasu; Sandeep Singh; Narendra Kumar; Indra Bir Singh; Munendra Singh (Environmental Monitoring and Assessment, 2021)

Mitochondrial remodelling—a vicious cycle in diabetic complications - Bhoomika Sherkhane; Gundu Chayanika; Anika Sood; Dharmendra Kumar Khatri; Shashi Bala Singh (Molecular Biology Reports, 2021)

Chemical composition and antimicrobial activity of the essential oil of senescent leaves of guava ( Psidium guajava L.) - Trishna Chaturvedi; Swati Singh; Indrajeet Nishad; Ajay Kumar; Neha Tiwari; Sudeep Tandon; Dharmendra Saikia; Ram Swaroop Verma (Natural Product Research, 2021)

PARP overactivation in neurological disorders - Vijay Kumar Arruri; Chayanika Gundu; Islauddin Khan; Dharmendra Kumar Khatri; Shashi Bala Singh (Molecular Biology Reports, 2021)

An Adaptive Technique to Detect and Remove Shadow from Drone Data - Ankush Agarwal; Sandeep Kumar; Dharmendra Singh (Journal of the Indian Society of Remote Sensing, 2021)

Chemical composition, bactericidal kinetics, mechanism of action, and anti-inflammatory activity of Isodon melissoides (Benth.) H. Hara essential oil - Ajay Kumar; Swati Singh; Anant Kumar; Dnyaneshwar Umrao Bawankule; Sudeep Tandon; Anil Kumar Singh; Ram Swaroop Verma; Dharmendra Saikia (Natural Product Research, 2021)

Exogenous phytase and xylanase supplementation of formulated diets for rohu (Labeo rohita): impact on haematology, histology and IGF I gene expression - Amit Ranjan; Sarvendra Kumar; Narottam Prasad Sahu; Kamal Kant Jain; Ashutosh Dharmendra Deo (Fish Physiology and Biochemistry, 2021)

Transcriptome skimming of lentil (Lens culinaris Medikus) cultivars with contrast reaction to salt stress - Dharmendra Singh; Chandan Kumar Singh; Jyoti Taunk; Shristi Sharma; Kishor Gaikwad; Vijayata Singh; Satish Kumar Sanwal; Deepti Singh; PC Sharma; Madan Pal (Functional & Integrative Genomics, 2021)

Correction to: Influence of Exogenous Silicon Addition on Aluminium Tolerance in Rice Seedlings - Vijay Pratap Singh; Durgesh Kumar Tripathi; Dharmendra Kumar; Devendra Kumar Chauhan (Biological Trace Element Research, 2021)

Forensic Study of Slope Failure Case During Heavy Rainfall: Suggested Preventative and Remedial Measures - Dharmendra Kumar Srivastava; Vaishali Sahu; H. B. Raghavendra (Geotechnical and Geological Engineering, 2020)

Development, Characterization, and Cross Species/Genera Transferability of Novel EST-SSR Markers in Lentil, with Their Molecular Applications - Dharmendra Singh; Chandan Kumar Singh; Kishor U Tribuvan; Punit Tyagi; Jyoti Taunk; Ram Sewak Singh Tomar; Shanti Kumari; Kuldeep Tripathi; Ashok Kumar; Kishor Gaikwad; Rajendra Kumar Yadav; Madan Pal (Plant Molecular Biology Reporter, 2020)

Influence of land configuration and organic sources of nutrient supply on productivity and quality of ginger (Zingiber officinale Rosc.) grown in Eastern Himalayas, India - Anup Das; Jayanta Layek; Subhash Babu; Manoj Kumar; Gulab Singh Yadav; Dharmendra Prasad Patel; Ramkrushna Gandhiji Idapuganti; Rattan Lal; Juri Buragohain (Environmental Sustainability, 2020)

Mapping human health risk by geostatistical method: a case study of mercury in drinking groundwater resource of the central ganga alluvial plain, northern India - Ashwani Raju; Anjali Singh; Nupur Srivastava; Sandeep Singh; Dharmendra Kumar Jigyasu; Munendra Singh (Environmental Monitoring and Assessment, 2019)

Molecular mapping of aluminium resistance loci based on root re-growth and Al-induced fluorescent signals (callose accumulation) in lentil (Lens culinaris Medikus) - Chandan Kumar Singh; Dharmendra Singh; Ram Sewak Singh Tomar; Sourabh Karwa; K. C. Upadhyaya; Madan Pal (Molecular Biology Reports, 2018)

Comparative evaluation of fermented and non-fermented de-oiled rice bran with or without exogenous enzymes supplementation in the diet of Labeo rohita (Hamilton, 1822) - Amit Ranjan; Narottam Prasad Sahu; Ashutosh Dharmendra Deo; H. Sanath Kumar; Sarvendra Kumar; Kamal Kant Jain (Fish Physiology and Biochemistry, 2018)

Breeding and culture status of Hilsa ( Tenualosa ilisha, Ham. 1822) in South Asia: a review - Amiya Kumar Sahoo; Md. Abdul Wahab; Michael Phillips; Anisur Rahman; Arun Padiyar; Velmurugu Puvanendran; Rama Bangera; Ben Belton; Dilip Kumar De; Dharmendra Kumar Meena; Bijay Kumar Behera; Anil Prakash Sharma; et al. (Reviews in Aquaculture, 2018)
The Hilsa shad, Tenualosa ilisha popularly known as ‘Hilsa’, is one of the most commercially important fish species in South Asian countries. The species is widely distributed from the Persian Gulf to Bay of Bengal and ascends into estuaries, rivers and brackish‐water lagoons of the Indo‐Pacific region. Recently, the availability of hilsa has drastically dwindled in aquatic systems across this region, due to anthropogenic pressures, mainly intensive fishing and river obstruction by dams and barrages. Climate change may also be contributing to the declining populations. Hence, there is an urgent need for conservation of the species. In addition, hilsa is of great cultural and economic importance among the peoples of Ganga‐Brahmaputra‐Meghna basin, with very high market demand and increasingly high prices, presently an average of around US$ 12 per kg for consumers both in India and Bangladesh. Many attempts at hilsa breeding and culture have been made across South Asia, particularly in India and Bangladesh, since the 1900s. To date, no breakthrough has been achieved in completing the life cycle in captivity. This review provides an insight into the status of artificial breeding, larval rearing and culture of this species, and identifies research gaps that need to be addressed by future aquaculture development programmes for hilsa in South Asia.

Drug targets in dormant Mycobacterium tuberculosis : can the conquest against tuberculosis become a reality? - Vivek Kumar Gupta; M. Madhan Kumar; Dharmendra Singh; Deepa Bisht; Shweta Sharma (Infectious Diseases, 2018)

Estimating carbon sequestration potential of existing agroforestry systems in India - Ajit; S. K. Dhyani; A. K. Handa; Ram Newaj; S. B. Chavan; Badre Alam; Rajendra Prasad; Asha Ram; R. H. Rizvi; Amit Kumar Jain; Uma; Dharmendra Tripathi; et al. (Agroforestry Systems, 2017)

Uptake, distribution, and remobilization of iron and zinc among various tissues of wheat–Aegilops substitution lines at different growth stages - Prachi Sharma; Imran Sheikh; Dharmendra Singh; Satish Kumar; Shailender Kumar Verma; Rahul Kumar; Pritesh Vyas; Harcharan Singh Dhaliwal (Acta Physiologiae Plantarum, 2017)

Synthesis and antimicrobial evaluation of ester-linked 1,4-disubstituted 1,2,3-triazoles with a furyl/thienyl moiety - C. P. Kaushik; Raj Luxmi; Dharmendra Singh; Ashwani Kumar (Molecular Diversity, 2017)

Uncovering leaf rust responsive miRNAs in wheat (Triticum aestivum L.) using high-throughput sequencing and prediction of their targets through degradome analysis - Dhananjay Kumar; Summi Dutta; Dharmendra Singh; Kumble Vinod Prabhu; Manish Kumar; Kunal Mukhopadhyay (Planta, 2017)

Bacteriophages and its applications: an overview - Sonika Sharma; Soumya Chatterjee; Sibnarayan Datta; Rishika Prasad; Dharmendra Dubey; Rajesh Kumar Prasad; Mohan G Vairale (Folia Microbiologica, 2017)

Application of Probiotics in Shrimp Aquaculture: Importance, Mechanisms of Action, and Methods of Administration - Vikash Kumar; Suvra Roy; Dharmendra Kumar Meena; Uttam Kumar Sarkar (Reviews in Fisheries Science & Aquaculture, 2016)

Magnaporthe oryzae aminosugar metabolism is essential for successful host colonization - Anil Kumar; Sumit Ghosh; Dharmendra Nath Bhatt; Alka Narula; Asis Datta (Environmental Microbiology, 2016)

Encapsulation of Mentha Oil in Chitosan Polymer Matrix Alleviates Skin Irritation - Nidhi Mishra; Vineet Kumar Rai; Kuldeep Singh Yadav; Priyam Sinha; Archana Kanaujia; Debabrata Chanda; Apurva Jakhmola; Dharmendra Saikia; Narayan Prasad Yadav (AAPS PharmSciTech, 2016)

M agnaporthe oryzae aminosugar metabolism is essential for successful host colonization - Anil Kumar; Sumit Ghosh; Dharmendra Nath Bhatt; Alka Narula; Asis Datta (Environmental Microbiology, 2016)
Summary Pathogens encounter and metabolize a range of host‐derived metabolites while proliferating inside the host. Our understanding of these metabolites and their metabolic processes has remained largely incomplete. We investigated the role of the M agnaporthe oryzae N ‐acetylglucosamine ( GlcNAc ) catabolic pathway during rice infection. The catabolic pathway is composed of a GlcNAc transporter ( MoNgt1 ), hexokinase(s), a GlcNAc ‐6‐phosphate deacetylase ( MoDac ) and a GlcN ‐6‐phosphate deaminase ( MoDeam ). A detailed characterization of the Δ mongt1 , Δ modac and Δ modeam null mutants revealed that a defect in GlcNAc catabolism impairs the pathogenicity of M . oryzae . These mutants showed severely reduced virulence in susceptible rice cultivar due to their inability to neutralize host‐derived reactive oxygen species and their failure to develop invasive hyphal growth within the host tissue. Interestingly, during oxidative stress, M . oryzae proliferated efficiently in GlcNAc ‐containing media compared with other sugars, and the expression of fungal antioxidant genes was upregulated following GlcNAc treatment. However, GlcNAc inhibited the growth of the Δ modac and Δ modeam mutants, and this growth inhibition was enhanced during oxidative stress. These results suggest that GlcNAc helps fungus to overcome oxidative stress inside its host, perhaps by activating an antioxidant defence. In the absence of a functional catabolic pathway, GlcNAc becomes toxic to the cells.

Characterization of interspecific hybrids of Triticum aestivum x Aegilops sp. without 5B chromosome for induced homoeologous pairing - Imran Sheikh; Prachi Sharma; Shailender Kumar Verma; Satish Kumar; Sachin Malik; Priyanka Mathpal; Upendra Kumar; Dharmendra Singh; Sundip Kumar; Vishal Chugh; Harcharan Singh Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2016)

Functional Screening and Molecular Characterization of Halophilic and Halotolerant Bacteria by 16S rRNA Gene Sequence Analysis - Bijay Kumar Behera; Priyanka Das; Jitendra Maharana; Dharmendra Kumar Meena; Tanmaya Kumar Sahu; A. R. Rao; Soumendranath Chatterjee; Bimal Prasanna Mohanty; Anil Prakash Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Buffalo (Bubalus bubalis) term amniotic-membrane-derived cells exhibited mesenchymal stem cells characteristics in vitro - Kaushalya Ghosh; Rajesh Kumar; Jarnail Singh; S. K. Gahlawat; Dharmendra Kumar; Naresh Lalaji Selokar; S. P. Yadav; B. R. Gulati; P. S. Yadav (In Vitro Cellular & Developmental Biology - Animal, 2015)

Speciation of atmospheric polycyclic aromatic hydrocarbons (PAHs) present during fog time collected submicron particles - Dharmendra Kumar Singh; Swati Sharma; Gazala Habib; Tarun Gupta (Environmental Science and Pollution Research, 2015)

Physiological and biochemical characteristics of Vigna species for Al stress tolerance - Dharmendra Singh; Madan Pal; Rajendra Singh; Chandan Kumar Singh; Ashish K. Chaturvedi (Acta Physiologiae Plantarum, 2015)

Stage-specific reprogramming of gene expression characterizes Lr48-mediated adult plant leaf rust resistance in wheat - Raman Dhariwal; Vijay Gahlaut; Bhaganagare R. Govindraj; Dharmendra Singh; Saloni Mathur; Shailendra Vyas; Rajib Bandopadhyay; Jitendra Paul Khurana; Akhilesh Kumar Tyagi; Kumble Vinod Prabhu; Kunal Mukhopadhyay; Harindra Singh Balyan; et al. (Functional & Integrative Genomics, 2015)

Buffalo Embryonic, Fetal and Adult Stem Cells: Progress and Challenges - Dharmendra Kumar; T. Anand; Selokar Naresh Lalaji; P. S. Yadav; Inderjeet Singh (Agricultural Research, 2015)

Phylogenetic analysis of the Listeria monocytogenes based on sequencing of 16S rRNA and hlyA genes - Dharmendra Kumar Soni; Suresh Kumar Dubey (Molecular Biology Reports, 2014)

Transcriptome-wide analysis of WRKY transcription factors in wheat and their leaf rust responsive expression profiling - Lopamudra Satapathy; Dharmendra Singh; Prashant Ranjan; Dhananjay Kumar; Manish Kumar; Kumble Vinod Prabhu; Kunal Mukhopadhyay (Molecular Genetics and Genomics, 2014)

In vitro antimicrobial activity of o-phenylenediamine-tert-butyl-N-1,2,3-triazole carbamate analogs - Manavendra Kumar Singh; Mayank Gangwar; Dharmendra Kumar; Ragini Tilak; Gopal Nath; Alka Agarwal (Medicinal Chemistry Research, 2014)

Stable carbon isotopes in dissolved inorganic carbon: extraction and implications for quantifying the contributions from silicate and carbonate weathering in the Krishna River system during peak discharge - Amzad H. Laskar; Naveen Gandhi; Kaustubh Thirumalai; Madhusudan G. Yadava; Rengaswamy Ramesh; Ramakant R. Mahajan; Dharmendra Kumar (Isotopes in Environmental and Health Studies, 2014)

Assessment of developmental potential of caprine cloned embryos with ooplasm replenishment under two culture media - R. Gopalakrishna; Dharmendra Kumar; Ajay Pratap Singh; Saurabh Kumar Pandey; Rakesh Ranjan; B. C. Sarkhel (In Vitro Cellular & Developmental Biology - Animal, 2014)

Field performance evaluation during fog-dominated wintertime of a newly developed denuder-equipped PM1 sampler - Dharmendra Kumar Singh; Lakshay; Tarun Gupta (Environmental Science and Pollution Research, 2014)

Phytoremediation Potential and Nutrient Status of Barringtonia acutangula Gaerth. Tree Seedlings Grown Under Different Chromium (CrVI) Treatments - Dharmendra Kumar; Durgesh Kumar Tripathi; Devendra Kumar Chauhan (Biological Trace Element Research, 2014)

Developmental potency of pre-implant parthenogenetic goat embryos: effect of activation protocols and culture media - Dharmendra Kumar; R. Gopalakrishna; Ajay P. Singh; Rakesh Ranjan; Saurabh K. Pandey; Bikash C. Sarkhel (In Vitro Cellular & Developmental Biology - Animal, 2014)

3-Methylcholanthrene Induces Neurotoxicity in Developing Neurons Derived from Human CD34+Thy1+ Stem Cells by Activation of Aryl Hydrocarbon Receptor - Abhishek K. Singh; Mahendra P. Kashyap; Vivek Kumar; Vinay K. Tripathi; Dharmendra K. Yadav; Firoz Khan; Sadaf Jahan; Vinay K. Khanna; Sanjay Yadav; Aditya B. Pant (NeuroMolecular Medicine, 2013)

Targeted spatio-temporal expression based characterization of state of infection and time-point of maximum defense in wheat NILs during leaf rust infection - Dharmendra Singh; Govindraj Bhaganagare; Rajib Bandopadhyay; Kumble Vinod Prabhu; Pushpendra Kumar Gupta; Kunal Mukhopadhyay (Molecular Biology Reports, 2012)

Impact of exogenous silicon addition on chromium uptake, growth, mineral elements, oxidative stress, antioxidant capacity, and leaf and root structures in rice seedlings exposed to hexavalent chromium - Durgesh Kumar Tripathi; Vijay Pratap Singh; Dharmendra Kumar; Devendra Kumar Chauhan (Acta Physiologiae Plantarum, 2012)

Influence of Exogenous Silicon Addition on Aluminium Tolerance in Rice Seedlings - Vijay Pratap Singh; Durgesh Kumar Tripathi; Dharmendra Kumar; Devendra Kumar Chauhan (Biological Trace Element Research, 2011)

Screening of pigeonpea genotypes for nutrient uptake efficiency under aluminium toxicity - Arbind Kumar Choudhary; Dharmendra Singh (Physiology and Molecular Biology of Plants, 2011)

Codon optimization of the major antigen encoding genes of diverse strains of influenza a virus - Indra Mani; Vijai Singh; Dharmendra Kumar Chaudhary; Pallavi Somvanshi; M. P. S. Negi (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Roles of RECQ helicases in recombination based DNA repair, genomic stability and aging - Dharmendra Kumar Singh; Byungchan Ahn; Vilhelm A. Bohr (Biogerontology, 2009)

Angiotensin II bi-directionally regulates cyclooxygenase-2 expression in intestinal epithelial cells - Tatsuo Tani; Rie Ayuzawa; Tetsuo Takagi; Tsutomu Kanehira; Dharmendra Kumar Maurya; Masaaki Tamura (Molecular and Cellular Biochemistry, 2008)

A new technique for monoconidial culture of the most aggressive isolate in a given population of Bipolaris sorokiniana, cause of foliar spot blotch in wheat and barley - Dharmendra Kumar; Ramesh Chand; Lal C. Prasad; Arun K. Joshi (World Journal of Microbiology and Biotechnology, 2007)

Preferential radioprotection to DNA of normal tissues by ferulic acid under ex vivo and in vivo conditions in tumor bearing mice - Dharmendra Kumar Maurya; Cherupally Krishnan Krishnan Nair (Molecular and Cellular Biochemistry, 2006)

Variability in Indian Isolates of Arthrobotrys dactyloides Drechsler: A Nematode-Trapping Fungus - Dharmendra Kumar; K.P. Singh (Current Microbiology, 2006)

Protection of cellular DNA from γ-radiation-induced damages and enhancement in DNA repair by troxerutin - Dharmendra Kumar Maurya; Sreedevi Balakrishnan; Veena Prakash Salvi; Cherupally Krishnan Krishnan Nair (Molecular and Cellular Biochemistry, 2005)

Radiation protection of DNA by ferulic acid under in vitro and in vivo conditions - Dharmendra Kumar Maurya; Veena Prakash Salvi; Cherupally Krishnan Krishnan Nair (Molecular and Cellular Biochemistry, 2005)